A viscoelastic, viscoplastic, and viscodamage constitutive model of salt rock for underground energy storage cavern. (March 2020) - Deng, Jianqiang; Liu, Yaoru; Yang, Qiang; Cui, Wei; Zhu, Yinbang; Liu, Yi; Li, Bingqi
Abstract: The underground energy storage in salt rock is of great strategic significance for ensuring the national energy safety and economic development. Due to the complex geological conditions, the construction of underground energy storage cavern in salt rock encounters great challenge and the long-term stability and safety issue of storage cavern in salt rock needs to be solved urgently. Based on the effective stress and the assumption of a small deformation, a unified constitutive model incorporating viscoelasticity, viscoplasticity, and viscodamage is developed by coupling the Kelvin-Voigt model, Duvaut-Lions model, and an improved Darabi viscodamage model to simulate the time-dependent mechanical behavior of salt rock for underground energy storage. The constitutive model is calibrated by experimental data to determine the parameters of viscoelasticity, viscoplasticity, and viscodamage. The model verification and discussion indicate that the constitutive model is able to effectively simulate the mechanical response of salt rock under different loading conditions and provide a safety guarantee for underground energy storage. The constitutive model is numerically implemented and successfully applied in long-term time-dependent deformation and failure analysis of underground energy storage cavern.